Solubilização in vitro de fosfato por Torulaspora globosa - Rocha, Renata Kühl (Universidade Federal de São Carlos, 2017)
Soil is an environment with great microbial diversity. Filamentous fungi and bacteria have been known for decades for the ability to stimulate plant development. Recently, studies have shown that yeasts are also capable of benefiting plants, for example, through the solubilization of inorganic phosphates. This work aims at a better understanding of the ability of rhizospheric yeasts in the solubilization of tricalcium phosphate. It also aims to study the influence of factors (pH, temperature and agitation) in the process. Initially, isolates of corn and sugarcane rhizosphere yeasts were made. The isolates were evaluated for the ability to solubilize tricalcium phosphate in solid medium BDYA. The isolate with the highest solubilization capacity was identified and evaluated for the solubilization capacity of tricalcium phosphate in NBRIP liquid medium at different temperature levels (20, 25 and 30 ° C), initial pH (3, 5 and 7) and agitation (0, 100, 150 and 200 rpm). Solubilization evaluations were also performed at 24-hour intervals, ranging from 1 to 7 days. Six isolates were obtained. All presented a positive result for solubilization. The yeast 6S01 (Torulaspora globosa) had the highest solubilization capacity. After five days, T. globosa solubilized 26 to 35% of the total phosphorus in the NBRIP culture medium. There was no significant difference for any of the environmental parameters tested. Assays performed in periods of 1 to 7 days showed that the yeast solubilized a maximum amount of phosphorus in 48 hours (42%). This makes it interesting for industrial and agricultural applications, since it has a fast solubilization process and can be used in a wide range of conditions. It was possible to understand that a higher cell growth is not related to the efficiency in the solubilization, and that acidification of the medium may be one of the main mechanisms used by yeast in the in vitro solubilization of tricalcium phosphate.
In vitro solubilization of phosphate by Torulaspora globosa
Keywords: Solubilização de fosfato in vitro; Promoção de crescimento vegetal; Torulaspora globosa; Phosphate solubilization in vitro; Plant growth promotion; CIENCIAS AGRARIAS